Salmonella Regulator STM0347 Mediates Flagellar Phase Variation via Hin Invertase - Wang, Hongou; Tang, Zhiheng; Xue, Baoshuai; Lu, Qinghui; Liu, Xiaoyun; Zou, Qinghua (International journal of molecular sciences, 2022)
Salmonella enterica is one of the most important food-borne pathogens, whose motility and virulence are highly related to flagella. Flagella alternatively express two kinds of surface antigen flagellin, FliC and FljB, in a phenomenon known as flagellar phase variation. The molecular mechanisms by which the switching orientation of the Hin-composed DNA segment mediates the expression of the fljBA promoter have been thoroughly illustrated. However, the precise regulators that control DNA strand exchange are barely understood. In this study, we found that a putative response regulator, STM0347, contributed to the phase variation of flagellin in S. Typhimurium. With quantitative proteomics and secretome profiling, a lack of STM0347 was confirmed to induce the transformation of flagellin from FliC to FljB. Real-time PCR and in vitro incubation of SMT0347 with the hin DNA segment suggested that STM0347 disturbed Hin-catalyzed DNA reversion via hin degradation, and the overexpression of Hin was sufficient to elicit flagellin variation. Subsequently, the Δstm0347 strain was outcompeted by its parental strain in HeLa cell invasion. Collectively, our results reveal the crucial role of STM0347 in Salmonella virulence and flagellar phase variation and highlight the complexity of the regulatory network of Hin-modulated flagellum phase variation in Salmonella.